Mind tools for managers 100 ways to be a better boss - Manktelow, James; Birkinshaw, Julian M. (Gildan, 2019)
The manager's must-have guide to excelling in all aspects of the job.
Online resource; title from title details screen (OverDrive, viewed May 8, 2019)
Keywords: Executive ability; Management; Aptitude pour la direction; Gestion; management; BUSINESS & ECONOMICS; Leadership; Downloadable audio books; Audiobooks; Livres audio